Benchmark Dose of Urinary Cadmium for Assessing Renal Tubular and Glomerular Function in a Cadmium-Polluted Area of Japan - Takuya Hayashi; Kazuhiro Nogawa; Yuuka Watanabe; Teruhiko Kido; Masaru Sakurai; Hideaki Nakagawa; Yasushi Suwazono (Toxics)
The aim of the present study was to apply an updated benchmark dose (BMD) approach to estimate reference urinary cadmium (U-Cd) for renal tubular and glomerular effects. This cross-sectional survey was conducted 30 years ago in 30 men and 44 women living in a Cd-polluted area and in 18 men and 18 women living in a non-polluted area. We applied an updated hybrid approach to estimate the BMDs and 95% lower confidence limits (BMDLs) of U-Cd for creatinine (Cr) clearance (CrCl), estimated glomerular filtration rate (eGFR), β2-microglobulin (β2-MG), and β2-MG tubular reabsorption (%TRβ2-MG). Using a benchmark response (BMR) of 5%, we estimated the BMDLs of U-Cd for adverse renal effect markers to be 2.9 (eGFR), 1.8 (β2-MG), 1.8 (%TRβ2-MG < 95%), and 3.6 μg/g Cr (%TRβ2-MG < 90%) in men, and 3.5 (CrCl), 2.5 (β2-MG), 2.6 (%TRβ2-MG < 95%), and 3.9 μg/g Cr (%TRβ2-MG < 90%) in women. The obtained BMDLs for tubular effects were 1.8–3.6 µg/g Cr and for glomerular effects were 2.9–3.5 µg/g Cr; these are not very high compared to the exposure levels in the general population. The BMDLs calculated in this study provide important information for measures regarding protecting general inhabitants or workers from the adverse health effects of Cd exposure.